Standardized assessment of seizures in patients with juvenile neuronal ceroid lipofuscinosis. (11th November 2014) - Augustine, Erika F; Adams, Heather R; Beck, Christopher A; Vierhile, Amy; Kwon, Jennifer; Rothberg, Paul G; Marshall, Frederick; Block, Robert; Dolan, James; Mink, Jonathan W; the Batten Study Group
<x xml:space="preserve">Abstract</x> Aim To evaluate seizure phenomenology, treatment, and course in individuals with juvenile neuronal ceroid lipofuscinosis (JNCL). Method Data from an ongoing natural history study of JNCL were analyzed using cross‐sectional and longitudinal methods. Seizures were evaluated with the Unified Batten Disease Rating Scale, a disease‐specific quantitative assessment tool. Results Eighty‐six children (44 males, 42 females) with JNCL were assessed at an average of three annual visits (range 1–11). Eighty‐six percent (n=74) experienced at least one seizure, most commonly generalized tonic–clonic, with mean age at onset of 9 years 7 months (SD 2y 10mo). Seizures were infrequent, typically occurring less often than once every 3 months, and were managed with one to two medications for most participants. Valproate (49%, n=36) and levetiracetam (41%, n=30) were the most commonly used seizure medications. Myoclonic seizures occurred infrequently (16%, n=14). Seizure severity did not vary by sex or genotype. Seizures showed mild worsening with increasing age. Interpretation The neuronal ceroid lipofuscinoses (NCLs) represent a group of disorders unified by neurodegeneration and symptoms of blindness, seizures, motor impairment, and dementia. While NCLs are considered in the differential diagnosis of progressive myoclonus epilepsy, we show that myoclonic seizures are infrequent in JNCL. This highlights the NCLs as consisting of genetically distinct disorders with differing natural history.